PERAN KELUARGA DALAM MENINGKATKAN KESADARAN KESEHATAN PADA REMAJA DENGAN OBESITAS DI WILAYAH KERJA PUSKESMAS PANCORAN JAKARTA SELATAN - Siti Nur Alizah; Haslindar Hatta; julfilkar Adnan Irnu (Politeknik Karya Husada, 2025)
Abstract Article Title. Obesity is the accumulation of excessive or abnorman fat which can couse suboptimal health. When the body mass index (BMI) exceeds 30, it is considered obese. Aim: This study aims to determine the role of the family in increasing knowledge and attitudes in adolescents with obesity. Method: This research uses an explanatory case study design by implementing Evidence Based Practice (EPB). Results: After being given nursing care for two weeks in three meetings, the results showed that the role of Mrs. M and Mrs. Y’s family was optimal in changing physical activity and eating patterns. Conclusion: The family has carried out its role well, An. R and An. K.F routinely carry out physical activities according to the established schedule, and maintain a regular diet . Key Words: Family role, Health awareness, Obesity, adolescents.